Hiscock, Albert. Interview about the Hazel Pearl, the Saladin, and how to make gun shells. - Barrett, Terra (2016)
Interview with Albert Hiscock of Champney's West, NL about the shipwrecks of the Hazel Pearl and the Saladin, and explanation of how to make gun shells. Albert Hiscock was born June 8th, 1935 in his family home in Champney’s West; 1:30 – Hiscock grew up in a family of 6 siblings; 1:58: the story of the sinking of the Hazel Pearl; 6:45 – discussion of the Saladin; 7:30 – how the crew walked off the Hazel Pearl onto the ice; 8:00 – explanation of a spar; 8:30 – how the spar ended up in front of the Heritage Home in Champney’s West; discussion of the oil that continued to leak up from the barrels of the Hazel Pearl; 9:53 – the story of the Saladin shipwreck; discussion of what was brought ashore by locals following the wreck; 11:55 – explanation of a Bosun’s chair; 13:05 – description and demonstration of the gun shell tools; 15:46 – description of the animals which were shot with the gun shells.